Hybrid Model of Student Career Development at SMK Negeri 2 Tulungagung - Yeni Tri Sesanti (BIRCU, 2023)
The Covid-19 pandemic as well as influential technological developments in the world of education, including changing career guidance classes. One learning model that is suitable for the needs of vocational students in the career guidance class is hybrid learning. Guidance and counseling teachers in vocational schools are required to be innovative and creative in career guidance learning. This research was conducted to find out the career guidance learning model for students at SMK Negeri 2 Tulungagung. This research is descriptive qualitative research, data from interviews and observations are presented and analyzed in the form of descriptive sentences that are easy to understand. The results show that counseling teachers can utilize technology and innovate in career guidance learning according to technological developments. BK teachers at SMK Negeri 2 Tulungagung carry out learning in career guidance classes through hybrid learning with online and offline combination models which are carried out in a scheduled, regular and effective manner to achieve learning objectives.